MEMBANGUN PROSES PERENCANAAN PENGELOLAAN DAERAH ALIRAN SUNGAI MIKRO SECARA PARTISIPATIF: SEBUAH PEMBELAJARAN (Developing a participatory planning process of micro-watershed management: a lesson learned) - Agung Budi Supangat; Dewi Retna Indrawati; Nining Wahyuningrum; Purwanto Purwanto; Syahrul Donie (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2020)
ABSTRACTPlanning is one of the very important stages in the micro watershed management. Difficulties and failures in the management of micro watershed are often caused by failures in the building of participatory planning processes with the community as well as a collaborative mechanism with relevant parties. This action research aims to find the applicable processes or stages of participatory planning based on the experience and evaluation of existing processes. The research was carried out in the Naruan micro watershed, Keduang sub-watershed, Bengawan Solo upper watershed. Some lessons learned that can be found from this research are as follows: 1) detailed baseline data related to the potential and vulnerability characteristics of micro watershed is very important to be understood before planning process; 2) micro watershed planning process cannot fully rely on community participation, but it should be a combination of top-down and participatory mechanism; 3) top-down planning is related to the provision of proper land management guidelines in the upstream area; 4) participatory planning is carried out when preparing of land use plans, determining the appropriate types of soil and water conservation activities, as well as identifying the resources contribution from the community as a form of participation; 5) collaborative action plans are needed to be built with relevant parties to support integrative and sustainable micro watershed management.Keywords: Collaboration; micro watershed; participation; planning ABSTRAKTahapan perencanaan merupakan bagian yang sangat penting dalam rangkaian kegiatan pengelolaan Daerah Aliran Sungai (DAS) skala operasional (DAS mikro). Kesulitan dan kegagalan pengelolaan DAS mikro seringkali bermula dari kegagalan dalam membangun proses perencanaan partisipatif bersama masyarakat dan kolaboratif dengan para pihak terkait. Kegiatan penelitian tindakan (action research) ini bertujuan untuk menemukan proses/tahapan perencanaan partisipatif yang lebih aplikatif berdasarkan pengalaman dan evaluasi proses yang sudah ada. Penelitian dilaksanakan di DAS Mikro Naruan, Sub DAS Keduang, DAS Bengawan Solo Hulu. Pelajaran yang dapat diambil dari kegiatan adalah sebagai berikut: 1) Basis data dasar (baseline data) detil terkait karakteristik potensi dan kerentanan wilayah DAS mikro sangat penting diketahui sebelum proses perencanaan; 2)Proses perencanaan pengelolaan DAS mikro tidak dapat sepenuhnya mengandalkan partisipasi masyarakat, tetapi perlu kombinasi antara sistem top down dan partisipatif; 3) Perencanaan yang sifatnya top down menyangkut pemberian rambu-rambu pengelolaan lahan yang benar di wilayah hulu DAS; 4) Perencanaan partisipatif dilakukan pada saat penyusunan rencana penggunaan/ pemanfaatan lahan, jenis kegiatan konservasi yang sesuai serta andil sumber daya dari masyarakat sebagai bentuk partisipasi; 5) Rencana kolaboratif perlu dibangun dengan para pihak terkait dalam rangka keterpaduan dan keberlanjutan kegiatan pengelolaan DAS mikro.Kata kunci: Kolaborasi; DAS mikro; partisipasi; perencanaan